Subsistence food production and marketing in Papua New Guinea : a research paper presented in partial fulfilment of the requirements for the degree of Master in Philosophy in Development Studies at Massey University - Peng, Peter Benjamen (Massey University, 1994)
Agriculture is the main component of the economic sector of the Less Developed Countries (LDC's) of Asia, Africa and Latin America. In most of these countries, which includes Papua New Guinea (PNG), subsistence agriculture dominates despite the tremendous advances in agricultural technology elsewhere, especially in Developed Countries, in the course of the twentieth century. The characteristic feature of these subsistence farms is low productivity which means small, if any, production surplus over consumption, which results in very little trade between the agriculture sector and other sectors of the country. In LDC's, this has often led to declining food production and increased dependence on imported food as the bulk of domestic food supply is produced by the subsistence sector. In PNG, very similar trends are noted. This paper examines some issues affecting smallholder agriculture and implications for increasing agricultural productivity in PNG. Specifically, the research problem and the focus of this study is firstly, how to increase subsistence food production and secondly, how to effectively move the rural surplus to urban consumers where it is required. To increase productivity, LDC's are faced with two choices; extend land area under cultivation if land is available or improve agricultural technology if land is scarce. While PNG is relatively well endowed with land (more than four times the average for developing countries) , much of the land is too mountainous to convert to arable land, with only less than 0.3 per cent of the land used for annual crops and grazing. The choice of strategy thus is determined by land. This paper shows that the PNG government has under-invested in agriculture, particularly subsistence agriculture. Further investment in research and technology is required, focusing especially on their farming systems. Traditional farmers are not traditionalist by choice. Agricultural techniques have been developed over centuries, through years of accumulated experience of generations of farmers. Extensive literature in agriculture economics show that traditional farmers cannot normally adopt technological innovations unless the circumstances in which they operate are first changed. The important role of marketing in economic development is also underplayed. It is a common fallacy to assume that markets when left to their own devices can lead to increased productivity and efficiency within the distribution system. Government intervention is also necessary in marketing to achieve social goals of self sufficiency in food production. This study attempts to demonstrate that given the right incentives, mostly institutional and technological, subsistence food production can be increased in PNG.
Keywords: Papua New Guinea; Agricultural productivity; Agriculture -- Economic aspects; Marketing; Food crops